Growth Effects of Cross-border Mergers and Acquisitions in European Transition Countries - Zvezdanović Lobanova, Jelena; Kračun, Davorin; Kavkler, Alenka (Naše gospodarstvo/Our economy, 2016)
This paper deals with the economic effect of cross-border mergers and acquisitions on GDP per capita in European transition countries for the 2000– 2014 period. Our analysis shows that cross-border mergers and acquisitions have a negative effect on GDP per capita in the current period, whereas their lagged level positively impacts output performance. We found that transition countries characterized by a higher quality of institutional setting have achieved a positive impact on GDP per capita.